The effectiveness of the parliamentary front on sport in the Brazilian National Congress between the World Cup and the Olympic Games - Dias Mendes, Alessandra; Nervo Codato, Adriano (Revista Brasileira de Ciência Política, 2019)
Parliamentary Fronts (PF) are supra party institutions in the Brazilian National Congress (BNC) that aim to exert political clout in policies regarding a specific subject. Although seldom studied, these institutions have proliferated, and their number peaked in the 54th legislature (2011- 2015) with a tally of 210. In this article, we analyse the effectiveness of the Mixed Parliamentary Front for Sports (FPE), which comprises 198 federal deputies (from 513) and 8 senators (from 81). As method we combined: prosopography of its members; network analysis formed by the decision- making arenas occupied by them at BNC; analysis of their political clout in the legislation for sport. Our results indicate a network mainly comprised of right-wing parties and professional politicians, which suggests a strong potential of political clout. Four theoretical constructs from their profile characteristics were correlated to the centrality within the network, which showed that political expertise and political specialization were crucial factors. We found 8 central members, reinforcing arguments from literature which proposed the existence of an operative nucleus within PF. In relation to the clout in the formulation of sport policy, the representatives belonging to the front were responsible for 94 (61%) proposals of the total of 246 bills presented in the field of sports. Moreover, they are not effective in approving these propositions, although more effective than others PF. Nevertheless, this research gave us a better understanding of policy formulation in complex political arenas, inaugurating a method and a theory to study effectiveness and centrality of this kind of institution.